Toward Therapeutic Targeting of Bone Marrow Leukemic Niche Protective Signals in B-Cell Acute Lymphoblastic Leukemia - Delahaye, Marjorie C.; Salem, Kaoutar-Insaf; Pelletier, Jeoffrey; Aurrand-Lions, Michel; Mancini, Stéphane J. C. (Frontiers in Oncology, 2021)
B-cell acute lymphoblastic leukemia (B-ALL) represents the malignant counterpart of bone marrow (BM) differentiating B cells and occurs most frequently in children. While new combinations of chemotherapeutic agents have dramatically improved the prognosis for young patients, disease outcome remains poor after relapse or in adult patients. This is likely due to heterogeneity of B-ALL response to treatment which relies not only on intrinsic properties of leukemic cells, but also on extrinsic protective cues transmitted by the tumor cell microenvironment. Alternatively, leukemic cells have the capacity to shape their microenvironment towards their needs. Most knowledge on the role of protective niches has emerged from the identification of mesenchymal and endothelial cells controlling hematopoietic stem cell self-renewal or B cell differentiation. In this review, we discuss the current knowledge about B-ALL protective niches and the development of therapies targeting the crosstalk between leukemic cells and their microenvironment.